Perawatan Pasca Melahirkan pada Etnis Bajo di Kelurahan Petoaha Kecamatan Nambo Kota Kendari - Ramadhani, Ramlah; Keke, Ahmat (Jurusan Antropologi Fakultas Ilmu Budaya Universitas Halu Oleo, 2024)
This research aims to find out what processes and factors encourage postnatal care among the Bajo tribe in Petoaha Village. The theory used is the medical system proposed by Foster & Anderson. The data collection technique is field research using ethnographic methods of involved observation and in-depth interviews. The data analysis technique used is descriptive qualitative. The research results show that (1) the postnatal care process has two stages, namely the first is the preparation stage, namely; hot boe (hot water), bidah (sarong), and cloth or gutta bittah (cloth or octopus stomach). The two implementation stages are; reading hot diboe prayers (reading prayers in hot water), hot boe bathing (hot water bath), using cloth or gutta bittah (using cloth or stomach octopus), and massaging bittah (massaging the stomach). (2) the factors that encourage treatment have several factors, namely the trust factor, meaning that the Bajo people have confidence in postnatal care because it has been a belief passed down from generation to generation and its success has been proven by themselves. The economic factor is that for the Bajo people, postnatal care from Sandro is much cheaper than getting treatment from a midwife. The health factor is so that postpartum mothers are not affected by disease and can speed up postnatal recovery.